The Theory of Concrete Mixture Vibratory Compacting - Maslov, Oleksandr; Batsaikhan, Janar; Salenko, Yulia (International Journal of Engineering and Technology, 2018)
Purpose. The creation of the compacting vibratory process theoretical basis enabling the assessment of the efficiency and the choice of rational modes of the vibration influence on the concrete mixture, based on the minimal energy input in the process of its compacting.Methodology. The paper contains the description of the mechanism of compacting under the action of external vibration forces whereat a variable tensely deformed condition occurs in the concrete mixture. In this case the primary structural links break, the links between its separate elements weaken, the final movements of mineral particles result in the creation of a more compact packing. As the basic factor determining the character of the compacting process, the authors propose to use the product of voltage and the velocity of the vibratory action, which presents the power of the vibratory action on the compacted medium.Results. The authors have obtained analytical expressions enabling the determination of the growth of the concrete mixture density in time function depending on the type of the vibratory load and the power of the applied vibratory action on the compacted medium. The paper contains the theoretical and experimental values of the specific work that provides compacting up to the values required by the technological norms depending on the consistence of the concrete mixture at vertical and horizontally directed vibrations.Conclusions. The authors have specified the existing hypothesis and proposed a more general power hypothesis of the process of vibratory compacting of concrete mixtures, applicable to the description of the vibration process and concrete media treatment by various vibratory mechanisms, tools and machines. One can use the obtained results to set the rational modes and duration of the vibratory action on the compacted medium depending on the amount and type of the specific work of compacting and also to determine the basic parameters of vibration machines of various technological purpose.Â Â